2016
DOI: 10.1186/s13048-016-0236-9
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive immunotherapy against ovarian cancer

Abstract: The standard front-line therapy for epithelial ovarian cancer (EOC) is combination of debulking surgery and platinum-based chemotherapy. Nevertheless, the majority of patients experience disease recurrence. Although extensive efforts to find new therapeutic options, cancer cells invariably develop drug resistance and disease progression. New therapeutic strategies are needed to improve prognosis of patients with advanced EOC.Recently, several preclinical and clinical studies investigated feasibility and activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Natural killer (NK) cells are involved in innate immunity and tumor surveillance; they also have the ability to recognize MHC class I or class I-like molecules on target cells through a unique class of receptors 34. NK cells are capable of exerting anti-tumor activity and lysing tumor cells without prior sensitization in an HLA-unrestricted way in contrast to TILs, for example.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Natural killer (NK) cells are involved in innate immunity and tumor surveillance; they also have the ability to recognize MHC class I or class I-like molecules on target cells through a unique class of receptors 34. NK cells are capable of exerting anti-tumor activity and lysing tumor cells without prior sensitization in an HLA-unrestricted way in contrast to TILs, for example.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Secondly, this also evidences the main location of resistant tumor EOC cells is within the peritoneal cavity thus representing a unique opportunity to target and eliminate them by local administrations using selected immune effectors. 4 This unique therapeutic opportunity is further supported by the results of studies that reported the feasibility and the clinical benefits of intraperitoneal adoptive transfers of lymphocytes (e.g., tumor-infiltrative T and Natural Killer (NK) lymphocytes) (see 5 for a review). Importantly, they suggested that their clinical efficacy could be enhanced by optimizing associations and positioning with standard therapeutic lines (e.g., maintenance).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, IFN-g is the major cytokine secreted by NK cells and has been shown to induce the permanent arrest of the growth of melanoma cells [77]. Ovarian cancer cells have high expression of MICA/B and ULBPs, which can activate NK cells through the active receptor NKG2D [51]. However, immunotherapies, which use NK cells for melanoma, ovarian cancer, and other solid tumors, can control disease progression but limitedly improve or abate disease [76,[78][79][80][81][82][83].…”
Section: Solid Tumorsmentioning
confidence: 99%
“…Immunotherapy using NK cells is a panspecific ACT immunotherapy that does not rely on the recognition of HLA-mediated tumor antigen [51]. Autologous and allogeneic NK cells can be both used in ACT immunotherapy because their safety and tolerability have been proven [52][53][54].…”
Section: Contribution Of Nk Cells To Cellular Immunotherapymentioning
confidence: 99%